The role of membrane charge on nanofiltration performance - Ribau Teixeira, Margarida (2012)
The effect of the pH on the ultrafiltration performance of natural surface waters with moderate NOM content was evaluated at a laboratory scale using a plate-and-frame polysulphone membrane of 47 kDa MWCO. The results at three different pH values (acid, neutral and basic) demonstrated the important role of the pH on the UF performance controlling the membrane – fouling matter interactions. The higher fluxes and lower NOM rejections obtained, at basic pH when compared to acid pH, are explained in terms of the variation of membrane and NOM charge, due to electrostatic repulsion and adsorption effects.